Pengembangan Media Pembelajaran Astronomi Rasi Bintang untuk Anak Usia Dini - Muhammad Qorib; Zailani Zailani; Radiman Radiman; Amrizal Amrizal; Abu Yazid Raisal (University of Muhammadiyah Sumatera Utara, 2021)
Astronomy is important to be introduced and taught to children because many things related to it are closely related to the actual lives of children. To introduce astronomy to children, the thing that is most considered as an obstacle is the availability of astronomical tools and the practical use of children learning astronomy. The method used in this research is Research and Development (research and development). Based on the assessments of the two validators for the media, the average value obtained is 76.88%. In terms of media, this constellation board is categorized as quite feasible to be developed. Based on the assessments of the two validators for the material, the average value obtained is 80.36%. From a media perspective, this constellation board is in the category worthy of being developed. The average validation from media experts and material experts was obtained at 78.62% with a fairly decent category.